Effect of acute moderate exercise on induced inflammation and arterial function in older adults. Issue 4 (24th January 2014) - Ranadive, Sushant Mohan; Kappus, Rebecca Marie; Cook, Marc D.; Yan, Huimin; Lane, Abbi Danielle; Woods, Jeffrey A.; Wilund, Kenneth R.; Iwamoto, Gary; Vanar, Vishwas; Tandon, Rudhir; Fernhall, Bo
Abstract : New Findings: What is the central question of this study? The aim of the study was to evaluate the effect of acute induced systemic inflammation on endothelial function, wave reflection and arterial function in older adults. What is the main finding and its importance? Acute inflammation induced by influenza vaccination did not affect endothelial function in older adults. These findings have never been shown in older adults, and they emphasize the importance of vascular function during systemic arterial inflammation. Acute inflammation reduces flow‐mediated vasodilatation and increases arterial stiffness in young healthy individuals. However, this response has not been studied in older adults. The aim of this study, therefore, was to evaluate the effect of acute induced systemic inflammation on endothelial function and wave reflection in older adults. Furthermore, an acute bout of moderate‐intensity aerobic exercise can be anti‐inflammatory. Taken together, we tested the hypothesis that acute moderate‐intensity endurance exercise, immediately preceding induced inflammation, would be protective against the negative effects of acute systemic inflammation on vascular function. Fifty‐nine healthy volunteers between 55 and 75 years of age were randomized to an exercise or a control group. Both groups received a vaccine (induced inflammation) and sham (saline) injection in a counterbalanced crossover design. Inflammatory markers, endothelial function (flow‐mediated vasodilatation) and measures of wave reflection and arterial stiffness were evaluated at baseline and at 24 and 48 h after injections. There were no significant differences in endothelial function and arterial stiffness between the exercise and control group after induced inflammation. The groups were then analysed together, and we found significant differences in the inflammatory markers 24 and 48 h after induction of acute inflammation compared with sham injection. However, flow‐mediated vasodilatation, augmentation index normalized for heart rate (AIx75) and β‐stiffness did not change significantly. Our results suggest that acute inflammation induced by influenza vaccination did not affect endothelial function in older adults.